Business Groups and Transnational Capitalism in Central America - Bull, Benedicte. author. aut Link
XI, 225 p.
Keywords: This book investigates Central America's political economy seen through the lens of its powerful business groups. It provides unique insight into their strategies when confronted with a globalized economy, their impact on development of the isthmus, and how they shape the political and economic institutions governing local varieties of capitalism.